Traditional Chinese Medicine characteristic treatment and nursing of intertrigo in a bedridden elderly patient (1例老年卧床患者间擦疹的中医特色联合治疗与护理) - LIANG Ying (梁颖) (中西医结合护理)
This paper summarized the Traditional Chinese Medicine(TCM) characteristic treatment and nursing management of intertrigo in a bedridden elderly patient. Based on the concept of holism in TCM, the combined treatment including TCM collapse stains, articular acupoint pressing, intradermal needling, as well as TCM nursing by syndrome differentiation, were carried out to relieve the clinical symptoms of intertrigo and improve the Zhang-Fu visceral organs and meridians function of the patient. (本文总结1例老年卧床患者间擦疹的中医特色联合治疗和护理经验。通过中医整体观念, 采用中药溻渍冷敷于患处, 联合刺激耳穴反应点, 通过经络传导, 给予皮内针温和、高频的持久刺激, 扶正培元, 疏风化湿, 调整经络肺腑功能, 改善间擦疹症状。)